Women’s Right, A Call for Life: A Critical Discourse Analysis of Pres. Donald Trump’s Speech for the 2020 March for Life - Juland D. Salayo (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2020)
Political ideologies and power are shaped by politiciansâ€™ manipulation of linguistic features that appeared in their public discourses. Employing transitivity system, this study investigated President Donald Trumpâ€™s speech during the 2020 â€œMarch for Lifeâ€ to identify the transitivity processes and to determine how these processes are assimilated in the said discourse.Â Findings revealed that 126 transitivity processes are dominantly material, relational, and mental.Â Being the first US president who graced this event, material processes constructed a self-statement of initiatives and efforts in preserving human life and his attack on his political nemesis as threats to the preservation of the value and dignity of life. Relational processes have constructed life-protection ideas by valuing the significance of the children and the unborn.Â Trumpâ€™s feelings toward the dignity of life are shaped by mental processes by his direct association to the public as among the advocates of human life. Â Ironically, transitivity processes have shown minimal involvement of women in his speech, contrary to the theme. Data prove that language employed in a public discourse builds power and ideologies that serve as the human framework to understand the mind of the speaker.